Modul Edukasi Untuk Peningkatan Pengetahuan Orang Tua dalam Melatih Anak Cerebral Palsy di Yogyakarta - Awanis, Almas; Astriyana, Sevy (Jurnal Farmasi (Journal of Pharmacy), 2018)
In Indonesia, children with cerebral palsy (CP) are classified into groups of Children whit special needs with a low prevalence of occurance. From the prefalence of low incidence does not mean without problems for parents in taking care of children with cerebral palsy. Support for children with special needs is proven by Yogyakarta being designated as a Child-Friendly City in 2016. However, in the preliminary study carried out there was still a rare exercise program carryout at home for supporting the achievement of training program for children with cerebral palsy. So, there needs to be education in form of modules that can help parent do the home program of exercise. This research was quantitative research with one group pre and posttest design. The study was conducted on Forty parents (biological relatives or babysitters) who accompanied children with CP sisorders during therapy session at the Rehabilitasi Medik RSA UGM, RSUD Yogyakarta and Wahana Keluarga Cerebral Palsy (WKCP) community. Bivariable analysis uses the paired t-test to find out the differenceinfluence before and after being given an educational module. Bivariable analysis showed that have an influence of education module distribution on the improvement of competence with the mean difference of 1.6 (p < 0,001). The result showed was an increase in parental knowledge of providing education module to perform home program for their children with cerebral palsy disorders.